PENGARUH PENERAPAN PEMBELAJARAN KOOPERATIF TIPE STAD TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN SEJARAH DI SMAN 5 PADANG - Hadi, Syarifah; Zafri, Zafri; Husnita, Liza (Pendidikan Sejarah, 2014)
Lock of studentâs fact interpretation understanding ability is caused by various of factors go such as history learning process which is still delivering of information that make student to be able to remind, the history learning aim is to practice students to think critical trough fact in history learning. One of effort to increase fact interpretation understanding in history learning is cooperative learning mode type STAD.the aim of the research is to know the effect of using cooperative learning model type STAD toward students history learning result at SMAN 5 Padang.the advantage of this research is to practice students to formulate fact to be concept and principle in order to increase studentâs history study result in finding material matter by self and increase creativity, studentsâinterest and also develop studentsâminf set toward history lesson material understanding. Kind of the research of quantitative research which data got trough direct eksperiment on XI IPS students of SMAN 5 Padang the research sample was got based on group random with arsumption that every group has same ability and habit in learning history. The sample was two classes that XI IPS 1 as experiment class and XI IPS 2 as control class. The research result shown the result study in interpretating achievement history fact experiment classhigher than control class. Itâs seen from differences of posttest average score experiment class as big as 5,71 and counrol class 4,75.It means that history fact interpretation result study increasing of experiment class higher than control class. From analysis of research result and explanation can be concluded that application of cooperative learning model type STAD had significant effect toward studentsâ study result in interpretating history material fact of XI IPS SMAN 5 Padang